Regulated earnings security: the relationship between employment protection and unemployment scarring over the Great Recession. (24th January 2021) - Gonalons-Pons, Pilar; Gangl, Markus
Abstract: The Great Recession raised the concern that employment protective institutions that are effective during macroeconomic stability might become counterproductive under growing macroeconomic volatility. We study this question by examining the relationship between employment protection legislation (EPL) and unemployment scars on earnings in 21 countries during the period surrounding the Great Recession. We use harmonized work history data for 21 countries from 2004 to 2014 and combine propensity score matching and multilevel-regression to estimate how earnings losses due to unemployment vary with the strength of labor market regulation and over changing macroeconomic conditions. We find that unemployment scarring is lower in contexts with robust employment protection, both under positive and negative macroeconomic environments. We also show that economic downturns intensify unemployment scarring significantly more in countries with weak EPL, largely because long-term unemployment is more strongly penalized. Taken together, our study finds that the positive effects of employment protection for workers remain robust during economic downturns.